Implementation Of Simple Linear Regression Algorithm In The Alumni Tracer Application Based on A Website at SMK Negeri 1 Sanaman Mantikei - Languju, Indri Kristin; Yusuf, Mohamad (IJISTECH (International Journal of Information System and Technology), 2023)
SMK Negeri 1 Sanaman Mantikei is one of the state vocational schools which has been standing for a long time and is well-known in Central Kalimantan. Therefore, it has many students from various regions, both within Kalimantan Island and outside the island. Of course, an impact on the increased number of graduates annually. Who are in different positions and roles. The existence of this Alumni Tracer application based on a website can be a solution for the school's need to collect data on its Alumni. This Tracer Alumni application is planned by Apex App Builder of a website application, employing the Rapid Application Development (RAD) method and utilizing Linear Regression Algorithm. The results of this research can predict the number of Alumni who have a job, providing estimations based on data within a specific time frame. The accuracy testing, conducted through manual Excel calculations, resulted in 336, while the accuracy testing with RapidMiner yielded a similar value of 336. This indicates that both manual and machine learning can be considered consistent.